Tahlil al-Jinsi fi Kitab al-Lughah al-‘Arabiyyah min I’dadi Wizarati asy-Syuun ad-Diniyyah - Khoirul Huda; Ida Rusnita (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
In the Arabic language book Curriculum 2013 for fourth-grade students, in the third lesson, the profession of gender-biased vocabulary was found: In that lesson, various types of professions for females and males are mentioned, such as the word (employee - female employee) except in the word “policeman - soldier - driver) it is mentioned for males only. And in the word (sewing - nurse) it is mentioned for females only. Based on what the researcher mentioned in the background of the research, the researcher’s problems are: How does gender analysis in the Arabic language book for primary school students based on the 2013 syllabus look from the context of the word and the presentation of images? How are disadvantages and advantages in the Arabic language textbook for primary school students based on the 2013 syllabus viewed from a gender context? The type of research used by the researcher in this research is library research. A gender analysis in the Arabic language book for primary school students based on the 2013 syllabus looks from the context of the word and the presentation of the images, and is done by counting the word used in the third, fourth, fifth and sixth grade book. Most of the words found in the Arabic language book are chapters that indicate that they are gender-responsive.